Efficacy of the calcium channel blocker amlodipine in the treatment of salt-sensitive hypertension in patients with different genetic status - N. V. Orlova; I. A. Alyautdinova; F. Yu. Kopylov; T. I. Boncalo; S. V. Shmeleva (Российский кардиологический журнал)
Aim. To study the effectiveness of the calcium channel blocker amlodipine in the treatment of salt-sensitive hypertension (HTN) and compare it with the genotypes of patients.Material and methods. The study involved 96 patients aged 42,7±5,2 years. There were following inclusion criteria: diagnosis — grade 1, stage 1 hypertension with low risk of cardiovascular events (CVEs). Before inclusion in the study, patients had not taken regular antihypertensive therapy for 3 months. Next, all patients underwent assessment of salt sensitivity of blood pressure according to the M. H. Weinberger method and, based on it, the participants were divided into salt-sensitive and salt-resistant. Regardless of the result, all patients were recommended to have a low-salt diet of 3-5 g/day, with subsequent 24-hour ambulatory blood pressure monitoring (ABPM) during the diet. In patients with ineffective diet, amlodipine was prescribed on day 26 at a dose of 2,5-5 mg once a day. The effectiveness of the drug was assessed by repeated ABPM. In addition, a genetic study was performed on 4 polymorphic variants of the genes AGT (T704C), AGT (C521T), AGTR1 (A1166C), AGTR2 (G1675A), ADD1 (G1378T), CYP11B2 (C344T), GNB3 (C825T), NOS3 (T786C), NOS3 (G894T), to determine their association with the effectiveness of a low-salt diet and amplodipine therapy.Results. In patients with grade 1, stage 1 hypertension with low risk of CVEs, the effectiveness of a low-salt diet and amlodipine monotherapy at a dose of 2,55 mg/day was revealed. The results of the study were confirmed by achieving target values of office blood pressure and ABPM. In hypertensive patients not sensitive to salt, amlodipine monotherapy was ineffective. The genotyping revealed a relationship between antihypertensive therapy with amlodipine in salt-sensitive patients and carriage of the GG polymorphism of the AGTR2 gene.Conclusion. The effectiveness of amlodipine and a low-salt diet in salt-sensitive patients with grade 1 hypertension, stage 1, low risk of CVEs with carriage of the GG genotype of the AGTR2 gene.